Gender Stereotyping in Sports - Miriam Marcén; Marina Morales; Almudena Sevilla (Institute of Labor Economics (IZA), 2020)
This paper contributes to the literature of gender differences in academic attainment by putting together several sources of data going back several decades to investigate how gender stereotypes and parental time investments shape sport choices of boys and girls during high school. Using data from the 2002-2019 National Federation of State High School Association, which provides information for every state on the total number of high school participants by gender in each sport, we document that states with more gender-equal norms are also states where boys and girls tend to break stereotypes when making sport choices in high school. We also identify parental time investments as being an important cultural-transmission mechanism.
Keywords: J10; J16; J18; 330; gender; stereotypes; bias; sports